2013
DOI: 10.1093/mnras/stt2255
|View full text |Cite
|
Sign up to set email alerts
|

On the development of the Papaloizou–Pringle instability of the black hole–torus systems and quasi-periodic oscillations

Abstract: We present the numerical study of dynamical instability of a pressure-supported relativistic torus, rotating around the black hole with a constant specific angular momentum on a fixed space-time background, in case of perturbation by a matter coming from the outer boundary. Two dimensional hydrodynamical equations are solved at equatorial plane using the HRSCS to study the effect of perturbation on the stable systems. We have found that the perturbed torus creates an instability which causes the gas falling in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…The relation among the pressure, rest mass density, and internal energy is defined using the perfect fluid equation of state P = (Γ − 1)ρ with Γ = 4/3. Initially a steady state accreated torus is produced using the appropriate values of the highest density of the torus ρ c = 1.140 x 10 −4 , the mass ratio of the black hole-torus M t /M BH = 0.1, the polytropic constant K = 4.969 x 10 −2 , the constant specific angular momentum 0 = 3.80, inner r in = 4.57 and outer, r out = 15.889, radii of the torus, cusp location r cusp = 4.57, and orbital period t orb = 151.6 at r c = 8.35 (Dönmez 2014a(Dönmez ,b, 2015.…”
Section: Equations Models and Initial Setupsmentioning
confidence: 99%
See 3 more Smart Citations
“…The relation among the pressure, rest mass density, and internal energy is defined using the perfect fluid equation of state P = (Γ − 1)ρ with Γ = 4/3. Initially a steady state accreated torus is produced using the appropriate values of the highest density of the torus ρ c = 1.140 x 10 −4 , the mass ratio of the black hole-torus M t /M BH = 0.1, the polytropic constant K = 4.969 x 10 −2 , the constant specific angular momentum 0 = 3.80, inner r in = 4.57 and outer, r out = 15.889, radii of the torus, cusp location r cusp = 4.57, and orbital period t orb = 151.6 at r c = 8.35 (Dönmez 2014a(Dönmez ,b, 2015.…”
Section: Equations Models and Initial Setupsmentioning
confidence: 99%
“…The outflow boundary condition is set up close to or far away from the black hole to avoid the unwanted oscillations. The more details about initial setups as well as boundaries used in our numerical simulation can be found in Dönmez (2014aDönmez ( ,b, 2015.…”
Section: Equations Models and Initial Setupsmentioning
confidence: 99%
See 2 more Smart Citations
“…The low density atmosphere, ρ atm = 10 the maximum density and pressure values at a well defined radial and angular coordinates for the stable torus, respectively. The numerical evolution of the black hole-torus system without any perturbation showed that the dynamic of steady-state torus was uninfluenced by the presence of the defined atmosphere [10]. The general form of the Kerr metric in Boyer-Lindquist coordinates is used to set up the black hole at the center of computational domain using a uniformly spaced grid along radial r and angular ϕ directions.…”
Section: Initial Setups and Definition Of The Physical Boundariesmentioning
confidence: 99%